Time-dependent reliability analysis of RC beams shear and flexural strengthened with CFRP subjected to harsh environmental deteriorations. (1st October 2019) - Firouzi, Afshin; Taki, Amirmasoud; Mohammadzadeh, Saeed
Highlights: Reliability analysis of reinforced concrete beams is conducted using first passage probability theory. The correlation between limit states increases the probability of failure of series system. Beam may experience brittle fracture during its service life due to its low steel stirrup ratio. Abstract: Time-dependent reliability analysis of existing reinforced concrete (RC) beams strengthened with externally bonded carbon fiber reinforced polymer (CFRP) wraps is conducted. Corrosion effect in terms of remaining cross sectional area of steel reinforcement is modelled as a non-stationary Gaussian process and the probability of failure is estimated as a solution to the first passage probability from the safe domain. Moreover, flexural and shear limit states are modeled in a series system formulation. It was found that the steel stirrup ratio strongly influenced the reliability of beams subject to harsh environments and in some cases beam may experience brittle fracture during its service life. Furthermore, it is found that the upper bound of the system probability of failure is significantly higher than its corresponding individual limit states due to correlation between flexural and shear failure modes.